A framework for the assessment of ICT maturity in becoming a WCU / Mas Anom Abdul Rashid and Mohd Noor Azman Othman - Abdul Rashid, Mas Anom; Othman, Mohd Noor Azman (Universiti Teknologi MARA Cawangan Pahang, 2005)
ICT has become a very important element in determining the standard and quality of efficiency of many organizations. The dynamic of ICT is so rapid that sometimes, we tend to overlook the necessity of measuring and assessing its development and sophistication in meeting the organizational needs and objectives set forth. The framework discussed in this paper can be considered as a guide to assess the maturity of UiTM’s ICT facilities in becoming a world class university.